Sensitive detection of Trypanosoma evansi infection by polymerase chain reaction targeting invariable surface glycoprotein gene - KUMAR, RAJENDER; GAUR, DEEPAK KUMAR; GOYAL, SACHIN KUMAR; SHARMA, PARVATI; KANKAR, SHASHI KANT; JAIN, SHIKHA; KUMAR, SANJAY (The Indian Journal of Animal Sciences, 2016)
Trypanosoma evansi, an extracellular haemoprotozoan parasite, causes surra in a wide range of domestic and wild animals. In the present study, a diagnostic PCR assay was developed using primers targeting invariable surface glycoprotein (ISG) gene of T. evansi, which amplified a 196 bp product. The DNA was extracted from purified trypanosomes and T. evansi infected mice blood, and serially diluted ranging from 20 ng/µl to 0.002 pg/µl and from 90 ng/µl to 0.009 pg/µl, respectively. The diagnostic sensitivity of the PCR assay was 0.02 ng/µl (2×101 parasites) and 0.09 ng/µl (1×102 parasites) with purified parasite DNA and infected mice blood DNA, respectively. The PCR assay was also performed on extracted genomic DNA from 86 blood samples from the field out of which 3 animals were found positive by ISG-PCR assay. The developed ISG gene based PCR assay could be employed for sensitive detection of early infection, sub-clinical status of trypanosomosis and drug efficacy studies in animals.